Dirofilariasis by Dirofilaria repens: an imported case and a brief review. Issue 5 (October 2015) - Baptista-Fernandes, Teresa; Rodrigues, Manuel; Domingues, Dulce; Monteiro, Lucília; Paixão, Paulo; Pereira, Patrícia; Tavares, Raquel; Rodrigues, Paulo; Maurício, Isabel; Belo, Silvana; Toscano, Cristina
Abstract Human infections caused by Dirofilaria repens, a cosmopolitan zoonotic parasitosis endemic in Southern and Eastern Europe and Asia still is an underdiagnosed infection due to parasite identification difficulties. Here, we report the first human case of subcutaneous dirofilariasis by D. repens diagnosed in Portugal. This was probably an imported case from India, as judged by epidemiological and clinical data. With this presentation we aim to alert clinicians for the emergence of vector-borne zoonoses associated with global warming and international travel. This case showed that differential diagnosis of D. repens in subcutaneous nodules is needed, in order to avoid further complications.